Efikasi Diri Akademik sebagai Mediator: Hubungan antara Dukungan Sosial dan Prokrastinasi Akademik pada Mahasiswa Magang - Juliana, Sarah Gracyntia; Tiatri, Sri; Beng, Jap Tji (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study originated in the importance of social support and academic self-efficacy for the success of college students, particularly those in internship programs that require independence. The research explores the relationships between social support from family and friends, academic self-efficacy, and academic procrastination among college students—an area that has not been extensively studied. This non-experimental quantitative study involved 316 college students (aged 18-24) selected through purposive sampling. The results of the mediation analysis indicate that academic self-efficacy partially mediates the relationship between social support from family and academic procrastination, while academic self-efficacy fully mediates the relationship between social support from friends and academic procrastination. These findings support previous theories and provide new insights into the differential effects of social support based on its source. This study contributes significantly to understanding the psychological mechanisms underlying these relationships and offers practical recommendations for improving academic performance among college students, such as developing support programs that focus not only on enhancing general social support but also on specifically boosting academic self-efficacy through skills training, individual mentoring, and other relevant strategies.